Some aspects of the comparative analysis of legal knowledge bases - Paliulionienė, Laima (Lietuvos matematikos rinkinys, 1999)
One of the tasks in the process of preparing new legislation is the comparative analysis of different versions of the legislation. In this article we propose how the analysis could be partly automated if the legislation is formalized and stored in a knowledge base. The algorithm is proposed to find differences between legislations by using certain test situations. The algorithm is based on derivation by model generation and it is grounded in the case when the knowledge bases are general logic programs.